2014
DOI: 10.1007/978-3-319-08783-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Building above Read-once Polynomials: Identity Testing and Hardness of Representation

Abstract: Abstract. Polynomial Identity Testing (PIT) algorithms have focussed on polynomials computed either by small alternation-depth arithmetic circuits, or by read-restricted formulas. Read-once polynomials (ROPs) are computed by read-once formulas (ROFs) and are the simplest of read-restricted polynomials. Building structures above these, we show:1. A deterministic polynomial-time non-black-box PIT algorithm for (2) · ·ROF. 2. Weak hardness of representation theorems for sums of powers of constant-free ROPs and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Applying the hardness of representation approach of Shpilka and Volkovich [76], Mahajan-Rao-Sreenivasaiah [51] showed how to develop a deterministic black-box PIT algorithm for multilinear polynomials computed by ∑ ∑ ∏ O (1) formulas. Independently, Forbes [21] (following Forbes-Shpilka [26]) showed that this lower bound can again be made to apply to leading monomials 16 (which implies a deterministic black-box PIT algorithm for all ∑ ∑ ∏ O (1) formulas, with the same complexity as Mahajan-Rao-Sreenivasaiah [51]). This leading monomial lower bound, which we now state, is important for its applications to polynomials with hard multiples.…”
Section: Depth-3 Powering Formulasmentioning
confidence: 99%
“…Applying the hardness of representation approach of Shpilka and Volkovich [76], Mahajan-Rao-Sreenivasaiah [51] showed how to develop a deterministic black-box PIT algorithm for multilinear polynomials computed by ∑ ∑ ∏ O (1) formulas. Independently, Forbes [21] (following Forbes-Shpilka [26]) showed that this lower bound can again be made to apply to leading monomials 16 (which implies a deterministic black-box PIT algorithm for all ∑ ∑ ∏ O (1) formulas, with the same complexity as Mahajan-Rao-Sreenivasaiah [51]). This leading monomial lower bound, which we now state, is important for its applications to polynomials with hard multiples.…”
Section: Depth-3 Powering Formulasmentioning
confidence: 99%